INVESTIGATING DRYING PROFILES OF NATIVE GINGER RHIZOMES USING CABINET DRYING TECHNIQUE - Nzekwe U, Ugwoke C. E. C (Research Journal of Agriculture (RJA), 2022)
Ginger (Zingiber Officinale Roscoe) is an ancient and essential medicinal spice with a rich history of cultivation across the globe. As one of the oldest spices and condiments, it holds significant cultural, economic, and health importance. Nigeria, a major global producer of ginger, contributes approximately 8% of the world’s ginger production, with Kaduna state being a prominent production hub. The country produces diverse varieties, including ’Tafin-Giwa’ and ’Yatsun-Biri,’ alongside indigenous types such as Umudike Ginger I (UG I) and Umudike Ginger II (UG II). These varieties flourish in different regions, with high yields and consequential economic implications. Drying is a prevalent preservation technique employed to extend the shelf life of various agricultural products. Thin layer drying, which focuses on moisture removal through evaporation, is a widely studied method. Its application ensures reduced microbial spoilage, minimized physical and chemical changes, and prolonged storage capacity. The drying process significantly impacts the quality of ginger and is crucial for the production of dried powder, ginger split dried, and extracts. Researchers continually explore innovative drying methods to reduce energy consumption and drying time while maintaining product quality. Understanding the drying behavior of agricultural products is vital for efficient storage, processing, and equipment design in post-harvest operations. Investigating the drying kinetics of ginger, especially the split and whole rhizomes, is a fundamental step towards optimizing drying methods and enhancing food productivity. Experimental and analytical studies play a pivotal role in improving agricultural product characteristics, preserving nutritional value, and enhancing appearance. This study aims to analyze the drying kinetics of different ginger varieties using a cabinet dryer, while also evaluating treatment effects on split and whole ginger rhizomes. The insights gained from this research will contribute to better post-harvest processing techniques, reduced losses, and increased income for farmers.